Glioblastoma in adults: a Society for Neuro-Oncology (SNO) and European Society of Neuro-Oncology (EANO) consensus review on current management and future directions - Wen, Patrick Y.; Weller, Michael; Lee, Eudocia Q; Touat, Mehdi; Khasraw, Mustafa; Rahman, Rifaquat; Platten, Michael; Lim, Michael; Winkler, Frank; Horbinski, Craig; Verhaak, Roel G W; Huang, Raymond Y; et al. (Neuro-Oncology, 2025)
Glioblastoma is the most common type of malignant primary brain tumor and a major cause of morbidity and mortality. In 2021, the World Health Organization updated the classification of Central Nervous System (CNS) tumors to restrict glioblastomas to isocitrate dehydrogenase-wildtype (IDHwt) tumors, improving understanding of the prognosis and optimal therapy for these tumors. This revision also enables more homogeneous populations of patients to be enrolled in clinical trials, facilitating the evaluation of novel therapies. In this updated consensus review from the Society for Neuro-Oncology (SNO) and the European Association of Neuro-Oncology (EANO), the current management of patients with glioblastoma is discussed. In addition, novel therapies such as immunotherapies, viral therapies, targeted molecular therapies, theranostics, and antibody-drug conjugates will be reviewed, as well as the current challenges and future directions for research.
Gesehen am 27.11.2025